Characterization of Cu-mineralized carbonate veins in the Alta-Kvænangen Tectonic Window, Norway - Svens, Ellen (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2024)
The Alta-Kvænangen Tectonic Window is part of a regional greenstone belt that formed around 2.3 Ga – 2.0 Ga. The Bergmark anticline in the area has gone through greenschist to amphibolite facies metamorphism and hosts Cu, Co and Au mineralizations in hydrothermal veins, albite felsite and chemical traps. The area was mined during the late 19th century mostly in trenches but it has still got exploration potential. This project will classify carbonate veins that are hosted within two gabbro units, compare orientations between the barren and mineralized veins as well as discuss the origin of the veins. The study area has been affected by multiple extensional and compressional events during the Svecokarelian orogeny (1.9 – 1.8 Ga) and regional hydrothermal alterations including an influx of Na + Ca ± K ± Fe. Major shear zones were activated and used for transporting fluids which are thought to have controlled the formation of mineralization in second- or even third-order structures. The veins were studied using field work, detailed mapping, optical microscopy as well as scanning electron microscopy (SEM) and structural analysis. Results gave three different types of hydrothermal veins: 1) Fe oxide veins, 2) calcite veins and 3) dolomite-plagioclase-quartz veins. All of them show strong signs of deformation and recrystallization all while the chalcopyrite mineralization is heterogeneously distributed and commonly more or less bornite-altered. The veins pinch and swell over short distances and are sinuous but with a general orientation. Albite haloes are common for the veins but far from all veins have haloes. There are at least two generations of veins as some were found to have offset others. Brecciation, tension gashes and faults are also found in the area apart from veins. From the field measurements, two groups of orientations could be determined: one with a SW-NE direction and the other in NW-SE direction, both with relatively steep dips. Considering all downhole measurements, no conclusive results could be ...